Comparative analysis of indexes of physical preparedness of footballers of professional commands of different level - Shalenko V.V; Pertsukhov A.A (Kharkov National Pedagogical University, 2010)
This paper deals with results of the research of physical preparedness of professional teams of footballers of different level. The pedagogical testing program of the physical skills level includes control exercised recommended by the scientific-methodical committee of Ukrainian Federation of Football. The article presents indices of physical preparedness of footballers of different playing roles of the top league teams of Ukrainian championship and first league of Ukrainian team championship. Differences of physical preparedness structure of goalkeepers, defenders, halfbacks and forwards are revealed.